Sweet taste receptor agonists attenuate macrophage IL‐1β expression and eosinophilic inflammation linked to autophagy deficiency in myeloid cells. Issue 8 (21st August 2022) - Lee, Jinju; Kim, So Jeong; Choi, Go Eun; Yi, Eunbi; Park, Hyo Jin; Choi, Woo Seon; Jang, Yong Ju; Kim, Hun Sik
Abstract: Background: Eosinophilic inflammation is a hallmark of refractory chronic rhinosinusitis (CRS) and considered a major therapeutic target. Autophagy deficiency in myeloid cells plays a causal role in eosinophilic CRS (ECRS) via macrophage IL‐1β overproduction, thereby suggesting autophagy regulation as a potential therapeutic modality. Trehalose is a disaccharide sugar with known pro‐autophagy activity and effective in alleviating diverse inflammatory diseases. We sought to investigate the therapeutic potential of autophagy‐enhancing agent, trehalose, or related sugar compounds, and the underlying mechanism focusing on macrophage IL‐1β production in ECRS pathogenesis. Methods: We investigated the therapeutic effects of trehalose and saccharin on macrophage IL‐1β production and eosinophilia in the mouse model of ECRS with myeloid cell‐specific autophagy‐related gene 7 ( Atg7 ) deletion. The mechanisms underlying their anti‐inflammatory effects were assessed using specific inhibitor, genetic knockdown or knockout, and overexpression of cognate receptors. Results: Unexpectedly, trehalose significantly attenuated eosinophilia and disease pathogenesis in ECRS mice caused by autophagy deficiency in myeloid cells. This autophagy‐independent effect was associated with reduced macrophage IL‐1β expression. Various sugars recapitulated the anti‐inflammatory effect of trehalose, and saccharin was particularly effective amongst other sugars. The mechanistic study revealed an involvement of sweet taste receptor (STR), especially T1R3, in alleviating macrophage IL‐1β production and eosinophilia in CRS, which was supported by genetic depletion of T1R3 or overexpression of T1R2/T1R3 in macrophages and treatment with the T1R3 antagonist gurmarin. Conclusion: Our results revealed a previously unappreciated anti‐inflammatory effect of STR agonists, particularly trehalose and saccharin, and may provide an alternative strategy to autophagy modulation in the ECRS treatment. Abstract : Trehalose and saccharin attenuated eosinophilic inflammation linked to myeloid autophagy deficiency in a murine model of ECRS. Therapeutic efficacy was associated with their anti‐inflammatory effects, particularly IL‐1β production by macrophages. Activation of sweet taste receptor but not autophagy contributed to the alleviation of eosinophilia and IL‐1β dysregulation.